The effect of waste wash water on the concrete properties - Suhaya, Sekeri (2012)
The disposal of leftover concrete and waste wash water from ready-mix concrete trucks is becoming an increasingly greater environmental concern. When an empty 9m readymix truck returns to the batch plant from the construction site, there is still approximately 200 to 400 kg of concrete adhering to the inside of the drum and mixing blades. It takes approximately 700 to 1300 L of water to wash this concrete out before it hardens inside the drum. Then this waste wash water is directly distributed to the drainage without any treatment that could bring environmental problems. The alternative solution is to recycle the waste wash water and use it as batch water to make fresh concrete. In this study analyzes the quality of this waste wash water. Then, tests were conducted on mortar. The waste wash water meets the ASTM C94 requirements on mixing water for ready-mix concrete. The aim of this study is to determine the compressive strength and drying shrinkage of the mortar. The specimens for compressive strength test were cured under water with different curing duration of 7, 28 and 60 days. For drying shrinkage the specimens were cured on air for 4, 11, 18 and 25 days. The results revealed the development of compressive strength were increase with increases of curing days. While the value of drying shrinkage that recorded is less during the curing durations. It was shown that the mortar using waste wash water produce better results than mortar using tap water. Thus, the use of waste wash water from ready mix truck should be considered for use in concrete mix which is to improve the properties of concrete at the same time reducing the environmental pollution.